Rotation and Spin and Position Operators in Relativistic Gravity and Quantum Electrodynamics - Robert F. O’Connell (Universe, 2020)
First, we examine how spin is treated in special relativity and the necessity of introducing spin supplementary conditions (SSC) and how they are related to the choice of a center-of-mass of a spinning particle. Next, we discuss quantum electrodynamics and the Foldy−Wouthuysen transformation which we note is a position operator identical to the Pryce−Newton−Wigner position operator. The classical version of the operators are shown to be essential for the treatment of classical relativistic particles in general relativity, of special interest being the case of binary systems (black holes/neutron stars) which emit gravitational radiation.